2018
DOI: 10.1080/03003930.2018.1541794
|View full text |Cite
|
Sign up to set email alerts
|

Community engagement in Australian local governments: a closer look and strategic implications

Abstract: Public input into decision-making through participatory and deliberative democratic practices has become a widely accepted and legislated responsibility of Australian local governments. At any one time, councils are leading submission processes, workshops and online surveys on a multitude of projects, ranging from long-term community strategic plans to public art projects. The increase in these practices has been exponential, leaving little time for critical reflection. The lack of empirical data to illustrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…One of the issues is the importance of interacting and collaborating with the community to increase internal awareness and legitimation. Christensen and McQuestin (2019) presented the findings of a census probing community engagement practice in Australia's local government. Their study focused on the aspects of frequency of council engaging, council engaging approach, factors driving the council community engagement, engagement process, and council engagement method (14).…”
Section: Community Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the issues is the importance of interacting and collaborating with the community to increase internal awareness and legitimation. Christensen and McQuestin (2019) presented the findings of a census probing community engagement practice in Australia's local government. Their study focused on the aspects of frequency of council engaging, council engaging approach, factors driving the council community engagement, engagement process, and council engagement method (14).…”
Section: Community Engagementmentioning
confidence: 99%
“…Christensen and McQuestin (2019) presented the findings of a census probing community engagement practice in Australia's local government. Their study focused on the aspects of frequency of council engaging, council engaging approach, factors driving the council community engagement, engagement process, and council engagement method (14). These aspects were considered important in designing smart engagement between the council and the community.…”
Section: Community Engagementmentioning
confidence: 99%
“…Community engagement seeks to increase inclusion and fairness. It is also part of the core business of local governments, required by legislation in every Australian state (Christensen and McQuestin 2019).…”
Section: Findings: Increasing Participation and Deliberationmentioning
confidence: 99%
“…This undesirable attitude toward the participation concept might be due to a complex array of reasons that starts with not wanting to deal with opposition from the community and does not end with the extra workload often associated with the participation process. Christensen and McQuestin (2019) found that the time required for citizen participation is the biggest challenge facing governmental representatives while delivering participatory planning projects, which might cause resistance or dis-appreciation. Finally, in terms of the availability of IT resources and the familiarity of utilizing ICT to facilitate participatory planning, the city's level of maturity for introducing DPP was found to be adequate.…”
Section: Factors Related To the Governmental Organizationmentioning
confidence: 99%